(untitled) (Fiep Bulletin - online, 2019)
The present work had as objective to present the importance of the ludic activities in the process of development andlearning of the child attended in the infantile education. Developmental stages should be known so that play activities not onlyplay the child’s pleasure in playing, but develop other skills that are essential for their integral development as the cognitive,social, motor, and affective areas. In order to carry out this work, we used bibliographical research and searched authors such asKISHIMOTO (2001), KRAMER (2006), SANTOS (2002) and others who approach conceptions about early childhood and theobjectivity of children’s participation through playfulness, in which play and play bring important development of their identity andautonomy to this age group. In addition to encouraging the awareness of parents and educators about working together tointroduce the toy in the child’s learning. Using games and games in the school space will make classes more enjoyable andenjoyable in order to allow the educator to achieve success in the classroom. This creation of spaces and times for games andgames is an important task of the teacher, because it is up to him to plan this space. The teacher needs to be aware that gamesand games will have an intention and meaning for that student. For Piaget (1998) play is essential in the life of the child. He pointsout two types of games, the exercise game that is the one that the child repeats a certain situation for pure pleasure, for havingappreciated its effects. And the symbolic play, which satisfies the child’s need not only to mentally recollect the event, but toperform the presentation. Therefore, we understand that play is a fundamental right of every child and each one must be in aposition to take advantage of educational opportunities aimed at satisfying their basic learning needs. Faced with this, it is up tothe school to offer opportunities for the construction of knowledge and development of the child through games, toys and games.Therefore, with the theoretical and practical knowledge about the stages of child development and the work with play activities inearly childhood education, one can analyze the importance and benefits for the overall development of the child in all aspects.